Pengaruh Kecepatan Putar Terhadap Tegangan Dan Frekuensi Generator Induksi 1 Fase 6 Kutub - Saputro, Dwi Aji, Agus Supardi, S.T., M.T (2016)
In Indonesia, the source of electrical energy has become an important needs for the people, but the lack of equal distribution of electrical energy source particularly in some isolated areas will lead to problems of electrical energy crisis. It required a replacement, one of them using an induction motor as a self excited induction generator which is a small-scale alternative power generation (stand alone). Induction generator has a simple, robust, easy to operate, a relatively affordable price, and easy maintenance. The weakness is the performance of how it works greatly affected by load. This study aims to analyze the influences of the rotational speed toward the output voltage and the frequency from the induction generator whether in loaded condition as well as without any loads. Induction motors are applied as self excited induction generator has a power specification 1 HP, 6 poles, 1 phase, 940 rpm. When it functioned as induction generator is required capacitors (excitation) with a value of 72 μF at the output terminal in order to produce a voltage. Induction generator in no load condition can produce voltage 107,4 to 264,7 volt and frequency 47,2 to 54,7 Hz when rotated at 950 rpm to 1150 rpm. When a resistive load between 40 to 200 watts with an initial velocity of 1050 rpm produces a voltage of 199,1 to 164,3 volts while loading energy-saving lamps from 24 to 120 volts produces 186,4 to 135,6 volts. The increase in power load resulted in a decrease in voltage and frequency of induction generator.